Balanço de massa de um sistema de tratamento convencional e eletrodiálise para dessalinização de água salobra - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The management of available water resources has been stood out as there is a greater demand for water by the population and productive activities, in a scenario where there are periods of drought and waste. In addition, it is important to consider the quality of the available water, which is not always the required quality. One of the parameters that can hinder water consumption is the presence of salts from natural or anthropogenic means. It appears as an important alternative the desalination processes of brackish water for water purification. In order to study alternatives for the removal of salts, a system of desalination of brackish water, on a bench scale, was implemented in the premises of the State University of Ponta Grossa (UEPG), in the municipality of Ponta Grossa, Paraná. The systems were evaluated globally and separately from the data of water production and consumption, calculating the mass balance for the different concentrations of total dissolved solids (TDS). The system consisted of a set of bench scale units that make up the conventional treatment (TC), followed by electrodialysis desalination (ED). Brackish water was obtained by mixing saline and fresh water, as a source of saline water were used wastewater treatment of reverse osmosis (total dissolved solids (TDS) = 9000 mg.L-1 ), available from the UEPG Laboratory and sea water (TDS = 23900 mg.L-1 ) from the city of Camboriú, Santa Catarina. Water from Alagados, Pitangui and Verde rivers were used as freshwater source in the municipality of Ponta Grossa, Paraná. In all, 3 experiments were performed in TC and 9 in ED, of which: the first TC experiment was with concentration of SDT 1000 ±180 mg.L-1 , followed by 3 DE tests for this same concentration; the second CT test was performed with SDT concentration of 2000 ±180 mg.L-1 , followed by 3 DE assays for this SDT concentration; the third TC experiment was for SDT concentration of 3000 ±180 mg.L-1 , followed by 3 ED assays. The volume of treated water (recovery rate) was on average in the overall process of 38.21% and separately from the DE of 64.97%. The removal of SDT in electrodialysis was on average higher than 82.71% for the different concentrations. The higher the initial concentration of TDS in the water flow to be desalinated, the greater the initial electric current, consequently, the greater mass discharge at the TDS concentration of 3000 ±180 mg.L-1.
Keywords: Água salobra; Eletrodiálise; Tratamento convencional; Balanço de massa; Taxa de recuperação; Brackish water; Electrodialysis; Conventional treatment; Mass balance; Recovery rate; CNPQ::ENGENHARIAS::ENGENHARIA CIVIL